Results of study feed barley varieties (Mongolian Journal of Agricultural Sciences, 2021)
Barley (Hordeum vulgare L.) ranks fourth among the cereals in worldwide production and is grown annually on 48 million hectares in a wide range of environments. Barley has also been used as animal fodder, as a source of fermentable material for beer and certain distilled beverages, and as a component of various health foods. Most of Barley seeds used for animal feed are usually containing high amount of protein and even straw is used for animal feed. About 60-85 percent of the world's harvested barley is used to feed pigs, cattle and sheep. In Mongolia, up to 90 percent of the total barley production is used for forage and green fodder. For the that reason, we have been studied some barley varieties and breeding lines for use green fodder and forage. The main goal of our study was to identify superior variety or lines with high yield and high amount of protein for animal feed. The methodology was approved by Scientific Union of IPAS. 4 barley varieties and breeding lines are used this study. Following measurements are recorded including yield and its compound elements, dry weight of biomass, and some biochemical and technological features. Main result showed that breeding lines I-22453, I-22484 had highest yield and protein content compared to control variety. Total yield of these breeding lines were higher than from 240 to 450 kg per hectare and protein content were higher than from 0.5 to 1 percent compared to check variety.  The analysis of variance revealed that total yield was significant due to main effect of variety. The highest grain yield was obtained at cv.I-22484 (1490 kg) among the variety treatment. Control variety Viner selected as a plant height, wet biomass weight and dry biomass weight and Shimt selected as a high nutrient content of the green grass.         Тэжээлийн арвайн шинэ сортуудАрвайн сортууд нь голдуу малын тэжээлд зориулагдсан уургийн агуулалт өндөр байдаг ба үрээс гадна гуурс сүрлийг нь хүртэл малын тэжээлд ашигладаг. Дэлхийн хэмжээгээр нийт хураан авч буй арвайн 60-85 хувийг гахай, үхэр, хонь зэрэг амьтны тэжээлд ашиглаж байна. Манай орны хувьд нийт үйлдвэрлэсэн бүтээгдэхүүний 90 хүртэл хувийг хүчит тэжээл болон ногоон тэжээлд ашиглаж байна. Иймд газар тариалангийн бүс нутгуудад арвайн сорт, дугааруудыг ногоон тэжээл болон хүчит тэжээлийн чиглэлээр ашиглах зорилгоор судаллаа. Судалгааг УГТХ-ийн эрдмийн зөвлөлөөр баталсан “Арвайн селекци” нэгдсэн арга зүйн дагуу үзэгдэл зүйн ажиглалт, тэсвэрийн үзүүлэлтүүд, ургац, ургацын бүтцийн үзүүлэлтүүд, хуурай массын ургац, биохими технологийн үзүүлэлтүүд гэх мэт нийт 26 үзүүлэлтээр 4 сорт, дугаарыг харьцуулан судаллаа. Судалгааны дүнгээр И-22453, И-22484 дугаарууд ургацаар жишиг сортоос 2.4-4.5 ц/га-гаар, уургийн агуулалт 0.5-1.0 %-иар илүү байж шалгарлаа. Сортуудаас ХББЗ0,5-ний ялгаагаар И-22484 дугаар 14.9 ц/га ургацтай байж шалгарав. Ногоон массын үзүүлэлтээр Винер сорт ургамлын өндөр, нойтон өвсний ургац, хуурай өвсний ургацаар, Шимт сорт ургацын зөрүү бага ч өвсөнд агуулагдах шимт чанарын агууламж давуу байгаа нь ногоон тэжээлд тариалахад илүү тохиромжтой байна. Түлхүүр үг: уураг, ургац, ногоон тэжээл, шимт чанар